MULTIFUNCTIONAL DEVELOPMENT OF RURAL AREAS OF KAZAKHSTANWITH THE APPLICATION OF THE UNIFIED MODEL OF TOURISM IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND THE GREEN ECONOMY - Temirbulatova, Madina; Borza, Mioara (European Scientific Journal, ESJ, 2015)
In Kazakhstan, until recently, public opinion, public policy and science, unfortunately, dominated by a narrow approach to defining the role and importance of rural development. In general, the concept of "rural development" and "agriculture" were considered as identical, respectively, the role and importance for the country’s rural areas were reduced only to provide food and agricultural raw materials. Despite some positive changes, to overcome the systemic crisis in the rural areas of Kazakhstan is not yet possible. Reducing the number of rural settlements and rural population, a growing gap between urban and rural residents on life expectancy remains a huge difference in the level of material well-being and access to social infrastructure. Natural-resource orientation of the development of rural economy leads to environmental degradation in rural areas. Weak binding of youth and brain drain in rural areas hinder modernization and innovative development of agricultural production. One of the areas of social and agrarian policy of rural development, put forward by many developed countries, was diversifying employment in order to create alternative activities. Changes in agricultural policy appeared to strengthen measures to support rural development. In these countries, in rural development programs, excluding the funds allocated for the development of agricultural production and food aid, a large amount of funds from the budget. Such attention to rural areas due to the fact that they often have significant natural and cultural potential that is not used and the development of which would improve the well-being of not only the villagers, but also the general population. Thus, the skillful use of the capacity of rural areas in the relevant socioeconomic conditions gave rise to the policy multifunction (multilateral) development areas, which could also be called a small village industrialization, based on the support and development of non-agricultural initiatives. Multifunctional development is interpreted not only to the economic growth of the village, but also the improvement of the situation in the field of demography, the quality level of the rural population and the overall development of the state. Multifunctional development associated with the introduction of agriculture in the space of an increasing number of new non-agricultural functions. The village thus ceases to be a housing space for farmers producing mainly raw materials, it becomes integrally associated with the part of the national product, where people are busy as agriculture and non-agricultural economic activities.